2018
DOI: 10.1111/nep.13064
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of acute kidney injury in a department of internal medicine in ABIDJAN (cote D'IVOIRE)

Abstract: The aetiologies are dominated by infections. The fatality rate is high and its risk factors are advanced age, low haemoglobin level, severe AKI, infection and drug intake. Prevention is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(37 reference statements)
2
2
0
Order By: Relevance
“…Indeed, a lack of response to treatment, persistent inflammatory markers and hemodynamic instability in septic patients with AKI are the most prominent prognostic factors. This is in alignment with previous studies from different countries [ 31 , 32 ]. A systematic review in 2013 of 154 large studies that evaluated the world incidence of AKI and associated mortality demonstrated a pooled AKI-associated mortality rates of 23.9% and that rate was declining over time [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, a lack of response to treatment, persistent inflammatory markers and hemodynamic instability in septic patients with AKI are the most prominent prognostic factors. This is in alignment with previous studies from different countries [ 31 , 32 ]. A systematic review in 2013 of 154 large studies that evaluated the world incidence of AKI and associated mortality demonstrated a pooled AKI-associated mortality rates of 23.9% and that rate was declining over time [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, a lack of response to treatment, persistent in ammatory markers and hemodynamic instability in septic patients with AKI are the most prominent prognostic factors. This is in alignment with previous studies from different countries [29,30]. A systematic review in 2013 of 154 large studies that evaluated the world incidence of AKI and associated mortality demonstrated a pooled AKI-associated mortality rates of 23.9% and that rate was declining over time [31].…”
Section: Discussionsupporting
confidence: 87%
“…In one systematic review, only 33% of adults and 64% of children received dialysis when required [ 15 ]. The presence of AKI in Africa is associated with significant mortality [ 3 , 14 , 16 ] and an increased risk of developing chronic kidney disease (CKD) [ 10 , 17 ].…”
Section: Introductionmentioning
confidence: 99%